1977
DOI: 10.1530/jrf.0.0510355
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the effects of vasopressin and oxytocin on rabbit myometrial activity and a possible mediation of prostaglandins

Abstract: Uterine responses to vasopressin and oxytocin were monitored in non-pregnant and 3- or 6-8-day-pregnant rabbits by recording the intrauterine pressure. Oxytocin stimulated uterine activity in all groups, but the effect of vasopressin was stimulatory in non-pregnant animals, inhibitory in those 3 days post coitum and weakly stimulatory in those later in pregnancy. Inhibition of prostaglandin (PG) synthesis, by the administration of indomethacin, reduced the spontaneous uterine activity as well as the responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…After copulation there is an initial rapid increase in activity followed by a gradual decline to quiescence by about Day 4 of pregnancy (Aref & Hafez, 1973). In the non-pregnant rabbit oxytocin and vasopressin both stimulate uterine activity (Harris, 1947;Laudanski, Âkerlund & Batra, 1977;Nissenson, Flouret & Hechter, 1978). The response to oxytocin is increased by oestrogen treatment and abolished by progesterone (Harris, 1947;Nissenson et al, 1978).…”
Section: Uterus (Non-gravid)mentioning
confidence: 99%
“…After copulation there is an initial rapid increase in activity followed by a gradual decline to quiescence by about Day 4 of pregnancy (Aref & Hafez, 1973). In the non-pregnant rabbit oxytocin and vasopressin both stimulate uterine activity (Harris, 1947;Laudanski, Âkerlund & Batra, 1977;Nissenson, Flouret & Hechter, 1978). The response to oxytocin is increased by oestrogen treatment and abolished by progesterone (Harris, 1947;Nissenson et al, 1978).…”
Section: Uterus (Non-gravid)mentioning
confidence: 99%
“…The difference between the pseudopregnant and pregnant rabbits in this respect was statistically significant (Table 1). The fact that there was no change in myometrial activity with PG infusion in the nonpregnant uterus, which is generally more sensitive than the pregnant uterus (Laudanski et al, 1977), indicates that the increased myometrial activity in the pseudopregnant does was not a result of a direct action of the infused PG on the myometrium. This is further supported by the observation that the uterine activity in the pseudopregnant rabbits did not change with the low amount of PG administered until the progesterone levels had started to decrease (see also Challis et al, 1974).…”
Section: Discussionmentioning
confidence: 89%
“…The spontaneous uterine activity in the non-pregnant rabbits before administration of PG (Text-fig. lc) was typical in pattern for this endocrine condition (lack of progesterone) with contractions of comparatively high amplitude (mean 16-4 mmHg), medium frequency (mean 10-4 pressure cycles/10 min) and long duration (see, for example, Porter, 1968;Laudanski et al, 1977). These recordings exhibited a regular type of myometrial activity and there was a distinct relaxation phase after each contraction (Text-fig.…”
Section: Spontaneous Uterine Activitymentioning
confidence: 85%
“…More recently Chan (1977) using rat isolated uteri has suggested that the myometrial receptors for oxytocin and those for prostaglandin are functionally separate and distinct and that the uterotonic action of oxytocin is independent of prostaglandin-participation. However, although the involvement of prostaglandin in the uterotonic action of oxytocin does not appear to be obligatory, it seems to be dependent upon the hormonal environment as demonstrated by Laudanski, Akerlund & Batra (1977) using rabbit uterus in vivo.…”
Section: Histologyxmentioning
confidence: 96%